2009
DOI: 10.3233/jad-2009-1073
|View full text |Cite
|
Sign up to set email alerts
|

Serial Susceptibility Weighted MRI Measures Brain Iron and Microbleeds in Dementia

Abstract: A new iron sensitive MR sequence (susceptibility weighted imaging -SWI) enabling the simultaneous quantitation of regional brain iron levels and brain microbleeds (BMB) has been acquired serially to study dementia. Cohorts of mildly cognitively impaired (MCI) elderly (n=73) and cognitively normal participants (n=33) have been serially evaluated for up to 50 months. SWI phase values (putative iron levels) in 14 brain regions were measured and the number of brain microbleeds (BMB) were counted for each SWI study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
98
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 60 publications
5
98
0
Order By: Relevance
“…Other studies found an association between CMBs and low cognitive performance 12 or cognitive decline. 13 This variability may be due to differences in study design with varying cohort sizes and composition (eg, absence of a control group, varying exclusion criteria) and variable definitions of cognitive impairment. In the present study, the control group at baseline included only subjects who were cognitively intact confirmed by extensive neuropsychological testing.…”
Section: Prevalence Of Cmbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies found an association between CMBs and low cognitive performance 12 or cognitive decline. 13 This variability may be due to differences in study design with varying cohort sizes and composition (eg, absence of a control group, varying exclusion criteria) and variable definitions of cognitive impairment. In the present study, the control group at baseline included only subjects who were cognitively intact confirmed by extensive neuropsychological testing.…”
Section: Prevalence Of Cmbsmentioning
confidence: 99%
“…[8][9][10][11] Their impact on cognition is still a matter of debate. Several studies supported a deleterious effect of CMBs, including increased prevalence in vascular dementia but also in Alzheimer disease, 3,[12][13][14] associations with poorer cognitive function in cross-sectional studies of patients with dementia, 15 lower A␤42 levels in the CSF in Alzheimer disease and vascular dementia, 16 and decreased frontal-executive performances at 5-year follow-up in patients with stroke. 17 However, negative data were also reported with no or marginal impact of CMBs in early Alzheimer disease (for a review see van der Flier 18 and Heringa et al 19 ) and in subjects with subcortical vascular cognitive impairment 20 and symptomatic small-vessel disease.…”
mentioning
confidence: 99%
“…Nowadays, susceptibility-weighted imaging (SWI) is increasingly used for the detection of microbleeds (28)(29)(30)(31)(32). In SWI the magnitude and phase images of the T2*-weighted scan are combined to create enhanced contrast between tissues with different susceptibilities (21).…”
Section: Discussionmentioning
confidence: 99%
“…Ferritin is primarily responsible for the storage of intracellular iron in a non-toxic form, and is a natural source of intrinsic MRI contrast in various tissues and organs (Genove et al, 2005). The level of ferritin and its iron content can be quantified by MRI, which has been widely used clinically to measure tissue iron in the human brain (Kirsch et al, 2009;Pfefferbaum et al, 2009;Yao et al, 2009), liver (Beaumont et al, 2009) and heart (Guo et al, 2009). Compared with PET imaging, MRI can provide a much higher spatial resolution, but at the sacrifice of lower sensitivity.…”
Section: Visualizing and Quantifying Siv-infected Cells In Vivomentioning
confidence: 99%